SIMULATION OF PEAK GROUND ACCELERATION AND PSEUDO SPECTRAL ACCELERATION OF PALU EARTHQUAKE SEPTEMBER 28TH 2018 - Amalia Nasruroh; Bambang Sunardi; Muhammad Fikri Hayqal Hiola; Hendri Subakti (Program Studi Fisika Universitas Negeri Jakarta, 2021)
The devastating earthquake Mw 7.4 hit Palu City, Central Sulawesi on September 28th, 2018, at 17:02:44 WIB. A high tsunami followed it. More than 2000 people died as a result of the earthquake and tsunami disaster. The latest evidence shows that the earthquake was categorized as a rare super shear earthquake. The earthquake shaking that hit Palu City is relatively large. Acceleration data are not available at the study site due to the lack of instrumentation in the area. The Authors present a simulation of peak ground acceleration (PGA) and pseudo-spectral acceleration (PSA) due to the earthquake in three locations Tatura Mall, Roa-Roa Hotel, and Antapura Hospital. PGA describes the maximum acceleration on the ground, while pseudo-spectral acceleration describes the acceleration of earthquake shaking from buildings with various floor numbers. Simulation of PGA and PSA to the three sites used three different Ground Motion Prediction Equation (GMPE) functions, BSSA14, CB14, and CY14, with the weighting of each Next Generation Attenuation (NGA) GMPE functions. The results of PGA simulation is about 0.22-0.23 g and show that in the three study site, it is more vulnerable to spectral acceleration period T=0.3 s or building with three floors or about 1-15 floors. These correlate with the level of damage caused by earthquakes which is more impact to relatively higher buildings.